PENGARUH PROFITABILITAS, AUDIT TENURE, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN SEKTOR KEUANGAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2022–2025 - Erika Aprilia Rahayu; Hestin Sri Widiawati; Erna Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of profitability, audit tenure, and the size of public accounting firms (KAP) on auditor switching in financial sector companies—specifically the banking sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2022–2025 period. A quantitative approach with a causality design was employed. Secondary data were obtained from annual financial reports published on the IDX official website. The research sample consisted of 44 banking companies selected using purposive sampling, yielding 176 observation units over four years. Data analysis was performed using logistic regression with IBM SPSS Statistics 23. The results indicate that partially, profitability, audit tenure, and KAP size do not significantly influence auditor switching. However, simultaneously, all three variables significantly affect auditor switching (Chi-Square = 44.656; sig. = 0.000). The Nagelkerke R Square value of 0.477 indicates that the three variables explain 47.7% of the variation in auditor switching. These findings imply that auditor switching is a complex phenomenon influenced by a combination of factors simultaneously.